A study on the legal framework for the protection and conservation of wild plants in Peninsular Malaysia / Mohamad Fitri Abd Rahim, Nurul 'Ain Abu Bakar and Siti Nur Hasnas Jafri - Abd Rahim, Mohamad Fitri; Abu Bakar, Nurul 'Ain; Jafri, Siti Nur Hasnas (2012)
This research paper aims to scrutinize the existing laws in conserving and protecting wild plants in Peninsular Malaysia. In comparison, we also look into the law which governs the wild plants in Sabah and Sarawak as both of these states specifically provides for provision for wild plants. Apart from that, we also look into the United Kingdom law to establish the legal benchmark. Based on the research that has been conducted, there are existing legislation which is relevant in protecting and conserving the wild plants. Nevertheless, the legislations are still inadequate. It was clearly shown that the laws are scattered in the sense that there are eight Acts that conserve the wild plants in Peninsular Malaysia but there is no single Act that specifically governs wild plants in the Peninsular. As such, it can be concluded that the existing law is still inadequate.